Problems of Mediation Implementation in Divorce Case Settlement at the Medan Religious Court - Afriansyah Afriansyah (AT-TAFAHUM: Journal of Law, 2026)
Mediation is a dispute resolution mechanism that must be taken before the examination of the subject matter in court as an effort to realize a peaceful settlement of disputes. Although it has been regulated in Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Courts, the success rate of mediation in divorce cases in Religious Courts is still relatively low. This study aims to analyze the problems of the implementation of mediation in the settlement of divorce cases at the Medan Religious Court and examine efforts to optimize its implementation. This research uses an empirical legal research method with an empirical juridical approach. Primary data was obtained through interviews with mediator judges of the Medan Religious Court, while secondary data was obtained through literature studies of laws and regulations, books, and scientific articles related to mediation. All data were analyzed qualitatively using a descriptive-analytical method. The results of the study showed that the low success rate of mediation was influenced by long-standing domestic conflicts, the strong desire of the parties to divorce, the perception of the public that considered mediation as a procedural formality, and the limited time of mediation implementation. This study also found that the effectiveness of mediation is not only determined by the existence of regulations, but also influenced by the competence of the mediator, institutional readiness, and legal awareness of the parties. Optimizing the implementation of mediation can be done through increasing the capacity of mediators, using mediation time more effectively, and strengthening legal education to the public through synergy between the Supreme Court, Religious Courts, and the Office of Religious Affairs. Thus, mediation can function optimally as a dispute resolution instrument that supports the realization of a simple, fast, low-cost, and peace-oriented judiciary.